Welcoming SEND families to early years settings. (2nd August 2022) - Withers, Caroline
Abstract : For many children with SEND, early years education will represent the first critical steps to independence outside the home. It is crucial that this experience is positive and inclusive, and a child is offered a nurturing environment where their needs are addressed.